Supplementation of feed and water after long-duration road transportation: The effects on welfare and rumen fermentation in goats - Xu, Ke; Yang, Kang; Yang, Yi; Wu, Wenxuan; Zhou, Chuanshe (Frontiers in Veterinary Science, 2023)
Water and feed are needed during long-duration road transportation of livestock. There is, however, limited information on the need to supply with water and feed at temporary holding stations after road transportation. This study aimed to evaluate the effect of providing water and feed at holding stations on the welfare of goats in a mimic surrounding. Twenty-four Guizhou Black goats were randomly allocated to three groups of eight goats each as follows: deprived of water and feed (TRT0), supplemented with water ad libitum (TRT1), and supplemented with water and feed ad libitum (TRT2). Blood and rumen fluid samples were collected before loading (PRE) and after transport (POST). Statistical analysis was performed via Proc MIXED of SAS. The 10-h road transportation period reduced body weight in TRT0-goats (P < 0.05) but not TRT1 and TRT2 (P > 0.05). TRT0 and TRT1 had POST plasma glucose concentrations above their PRE values (P < 0.05). The PRE-plasma urea nitrogen levels were higher in TRT2 over TRT0 (P < 0.05), while TRT1 increased over TRT0 in response to POST-PUN levels. The POST non-esterified fatty acid concentration was higher for TRT0 compared to that in TRT1 and TRT2 (P < 0.05). No difference was observed for plasma profiles of malondialdehyde and superoxide dismutase (P > 0.05). TRT2 had higher POST glutathione peroxidase activity than TRT0 and TRT1 (P < 0.05). TRT0 had higher POST plasma glucagon relative to TRT2 (P < 0.05), and had increased values compared to their own PRE level as a result of road transportation (P < 0.05). TRT2 resulted in a lower POST plasma heat-stressed protein-70 (HSP-70) level than TRT0. There was no difference in ruminal pH (P > 0.05). Ruminal total VFA (acetate, propionate, butyrate), and NH3-ammonia profiles showed a decrease (P < 0.05) after transportation in all groups. Ruminal microcrystalline cellulose, xylanase, cellobiase, and carboxymethyl cellulose activities were unaffected (P > 0.05). These combined results imply that water and feed supplementation can effectively alleviate stress responses in goats subjected to road transportation, and emphasize the necessity to establish water and feed supplies even at a temporary holding pens.